Sereal Bekatul (SERENA) Berbasis Mixing Extrusion sebagai Alternatif Sarapan untuk Perbaikan Gizi Masyarakat - Komalasari, Lala; Tomi, Tomi; Falya, Yuniarti (Kolaborasi Masyarakat, 2025)
Nutritional issues such as low fiber and energy intake at breakfast remain common in Indonesia. This study developed a functional cereal product using rice bran (Bekatul) sourced from Sampiran Village, Talun District, Cirebon Regency, produced through a mixing-extrusion method involving local residents. Using a descriptive experimental approach, the research included product formulation, nutritional analysis, organoleptic testing, and shelf-life estimation via Accelerated Shelf-Life Testing (ASLT). The final product contained, per 100 g, 6 g protein, 16 g fat, 70 g carbohydrates, 7 g sugar, 516 mg sodium, and 448 kcal, sufficient to meet daily breakfast energy needs. Organoleptic results showed a visually appealing purplish-brown color, a sweet and savory taste, a pleasant aroma without rancidity, and a crunchy yet not overly hard texture. The cereal’s estimated shelf life at room temperature (20–25 °C) was 86 days. Overall, rice bran cereal demonstrates potential as a nutritious, locally sourced functional food that supports improved community nutrition.